The Rhetorical and Argumentative Relevance of "Extreme Consequence" in Advertising - Mazzali-Lurati, Sabrina; Pollaroli, Chiara; Marcantonio, Daniela (Informal Logic, 2019)
The “extreme consequence” is a very common pattern in advertising messages that presents an odd, even negative, situation resulting from the use of the advertised product as a good reason to buy it. By analyzing selected advertisements employing this pattern using the conceptual integration theory and the Argumentum Model of Topics, we aim to understand how “extreme consequence” works at the rhetorical and argumentative levels. The analyses allow us to detect the typical, generic, cognitive, and argumentative structure underlying the pattern and to identify the rhetorical and argumentative role played by its main components, namely exaggeration and cause-effect relation.